RETRACTED: Roles of Multiple Entrepreneurial Environments and Individual Risk Propensity in Shaping Employee Entrepreneurship: Empirical Investigation From China - Zeng, Kai; Wang, Duanxu; Li, Zhengwei; Xu, Yujing; Zheng, Xiaofen (Frontiers in Psychology, 2022)
While prior literature has widely acknowledged that entrepreneurial environment significantly fertilize entrepreneurship, the impact of workplace receives limited attention and the vital role of organizations in linking social entrepreneurial environment and employee entrepreneurship has been largely ignored. Therefore, this study aims to unfold how multiple entrepreneurial environments (i.e., social, organizational and interpersonal factors) shape employee entrepreneurship, and then further reveal how such relationships vary with employees’ risk propensity. Drawn on the theoretical lens of mindsponge process, which offers an explanation of why and how organization and individual adopt new values through cost-benefit analysis, we propose a research model to explain the influence mechanisms of social entrepreneurial environment on cost-benefit analysis of both organizations and individual employees. Specifically, given that organizations deeply embedded in the society need to balance the costs and benefits under the pressure of social entrepreneurial environment, social entrepreneurial environment affect organizational entrepreneurial environment (i.e., organizational hostility towards employee entrepreneurship). Similarly, employees’ cost-benefit analysis under the pressure of organizational hostility will influence their entrepreneurial intentions. Through analyzing the data collected from a two-wave survey with 220 employees, we show that organizational hostility towards employee entrepreneurship plays a mediating role between social entrepreneurial environment and employees’ entrepreneurial intentions. In addition, such mediation relationship is moderated by coworkers’ unethical behaviors during their entrepreneurship and employees’ risk propensity, which are expected to influence organizations’ and employees’ cost-benefit analysis respectively.